APLIKASI PEMANFAATAN GAMBUT UNTUK PENGEMBANGAN ZONA PRODUKTIF DI BANTARAN SUNGAI SIAK - E. Hanggari Sittadewi (Jurnal Rekayasa Lingkungan)
The productive zone in Siak river’s corridor can utilized to increase the social economic after due consideration of conservation aspect. Land of that zone can be developed for production of horticulture or plantation. Choosing peat compost (an organic fertilizer) to improve soil quality in the productive zone of Siak river’s corridor is a good practice due to peat function to support plant growth both qualitatively and quantitatively. In addition the usage also decrease agriculturalbase pollution. This paper describe experimentation result the peat organic fertilization to develop productive zone in the Siak river’s corridor. The use of peat organic fertilizaton in the productive zone of Siak river’s corridor, have positive growth’s respon for horticulture (chilli, pakcoy, terong belanda, cucumber), no nutrient deficiencies and have good yield.Key words : productive zone in Siak river’s corridor, peat compost.